2021
DOI: 10.1007/978-3-030-87358-5_4
|View full text |Cite
|
Sign up to set email alerts
|

UAV Track Planning Algorithm Based on Graph Attention Network and Deep Q Network

Abstract: This study investigates the enhancement of the traditional Deep Q-Network (DQN) trader model through the integration of cutting-edge techniques such as Prioritized Experience Replay, Regularized Q-Learning, Noisy Networks, Dueling DQN, and Double DQN. Through rigorous empirical testing on a spectrum of financial instruments including BTC/USD and AAPL, the research delineates clear performance improvements over the original model. The augmented DQN trader showcases remarkable gains, with the DQN-vanilla variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It employed a partly visible state that focuses primarily on the UAV's immediate surroundings rather than the whole deployment region, which results in a slow UAV and substantial computing costs. UAV track planning approach based on Graph Attention Network and Deep Q Network to solve the problem of mission failure caused by erroneous data acquired from UAV during flight present by [128]. It uses the camera to capture photographs and then runs them through a ResNet that has previously been trained to recognize and classify different items within those pictures.…”
Section: B Uavs Collision Avoidance Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…It employed a partly visible state that focuses primarily on the UAV's immediate surroundings rather than the whole deployment region, which results in a slow UAV and substantial computing costs. UAV track planning approach based on Graph Attention Network and Deep Q Network to solve the problem of mission failure caused by erroneous data acquired from UAV during flight present by [128]. It uses the camera to capture photographs and then runs them through a ResNet that has previously been trained to recognize and classify different items within those pictures.…”
Section: B Uavs Collision Avoidance Algorithmsmentioning
confidence: 99%
“…Geometric [135], [143], force field [131], [132], optimum trajectory [119], and Markov Decision Process (MDP) [108], [110] approaches are the most used [144]. Numerous suggested algorithms using mathematical approaches [5], [72], [89], [105], [129] and ML [100], [128] need a strong processor and memory space, which cannot accommodate most UAVs operating in the real world. On the other hand, owing to the delay and time necessary for setting up and training these algorithms, their implementation in real-time is not anticipated, and the present latency may result in operation failure or drone collisions.…”
Section: B Algorithm's Typementioning
confidence: 99%
“…2019 ) and graph convolutional networks (GCNs) (Hu et al. 2022 ; Zhu et al. 2019 ), have been proposed to capture multi-level features and global dependencies.…”
Section: Related Workmentioning
confidence: 99%
“…The attention mechanism is a method for rapidly selecting high-value information from huge amounts of information. Based on this mechanism, Hu et al [33] developed a runoff forecasting model and predicted the runoff of the basin, and the results demonstrated that this improved method can enhance the accuracy of runoff forecasting.…”
Section: Introductionmentioning
confidence: 99%